An Analysis of Questioning the Author (QTA) As A Technique To Motivate Senior High School Students in Reading Skill - Halimatul Intihan; Siti Sarah Fitriani; Diana Achmad (Research in English and Education Journal, 2022)
This study aims to find out the steps of using the Questioning the Author (QtA) technique to motivate senior high school students in teaching reading. Besides that, it also aims to test the effectiveness of teachers in teaching reading by using the Questioning the Author technique in teaching. This type of research is a library research. This research technique uses content analysis design. Here the data is taken from the internet and libraries or from other sources such as books, journals, articles and others. The conclusion of this study is there are several steps and techniques that are effective for students and teachers in applying the Questioning the Author technique. Based on the results of several researchers’ study, it shows that every step and technique used in the teaching and learning process is proven that can improve and motivate them in reading skills during teaching and learning process, both teachers and students get satisfactory results.